(untitled) (Dhaka University Journal of Biological Sciences, 2018)
A total of 17 pteridophyte species belonging to 11 genera and 9 families have been identified from Adampur forest of Moulvibazar district in Bangladesh are dealt with. Updated nomenclature with important synonyms, family name, English name, local name, citation of the specimen examined and a crisp description has been furnished under each species. Photographs of the species have been provided for easy identification. The voucher specimens have been deposited in the Dhaka University Salar Khan Herbarium, Department of Botany, University of Dhaka. Dhaka Univ. J. Biol. Sci. 27(1): 101-111, 2018 (January)